2008
DOI: 10.1108/07363760810870662
|View full text |Cite
|
Sign up to set email alerts
|

Digital piracy of MP3s: consumer and ethical predispositions

Abstract: Purpose -Illegal downloading of music has become an inexorable and rampant activity particularly among college students who have been little deterred by industry legal actions. The purpose of this research is to examine NOT THE PUBLISHED VERSION; this is the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation at the bottom of the page. Marketing, Vol 25, No. 3 (2008): pg. 167-178. DOI. This article is © Emerald and permission has been granted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(156 citation statements)
references
References 37 publications
4
138
0
14
Order By: Relevance
“…Hinduja (2008) explains that the behaviour of deindividuating reduces self-awareness and self-regulation which in turn may facilitate individual digital piracy behaviour. Secondly, although one would expect that a fear of punishment would be a deterrent against illegal downloading (Lysonski and Durvasula 2008) the threat of prosecution did not in fact increase the willingness of students to buy their software products (Hsu and Shiue 2008). It would seem that the illegal downloader's perception of risk is low.…”
Section: Risk and Punishmentmentioning
confidence: 99%
“…Hinduja (2008) explains that the behaviour of deindividuating reduces self-awareness and self-regulation which in turn may facilitate individual digital piracy behaviour. Secondly, although one would expect that a fear of punishment would be a deterrent against illegal downloading (Lysonski and Durvasula 2008) the threat of prosecution did not in fact increase the willingness of students to buy their software products (Hsu and Shiue 2008). It would seem that the illegal downloader's perception of risk is low.…”
Section: Risk and Punishmentmentioning
confidence: 99%
“…Product counterfeiting and piracy of either luxury consumer or industrial goods is a severe global problem and is prevailing more in developing countries than in developed nations. The fact is that the consumers only perceive the social benefits of fake products, they do not bother that their behavior is harmful to a specific industry or that it can lead to a social cost (Lysonski and Durvasula, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ramayah et al (2009) looked at piracy amongst university students and found that habit was in fact the strongest key driver; leading to calls for further awareness campaigns on the negative effects of piracy, including the illegality and unethical nature of it. Lysonski and Durvasula (2008) also conducted research amongst college students which showed that downloading amongst this section of the population continues at a high rate. Although fear of the consequences of being caught did affect the propensity to download illegally, a strong key driver of these results was that piracy is still not considered to be ethically wrong.…”
Section: The Bad (Record Industry Dies Slowly)mentioning
confidence: 99%